2016
DOI: 10.1155/2016/4684268
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells, Tumor Cell Transition, and Tumor Progression in Solid Malignancies: New Hints for NK-Based Immunotherapy?

Abstract: Several evidences suggest that NK cells can patrol the body and eliminate tumors in their initial phases but may hardly control established solid tumors. Multiple factors, including the transition of tumor cells towards a proinvasive/prometastatic phenotype, the immunosuppressive effect of the tumor microenvironment, and the tumor structure complexity, may account for limited NK cell efficacy. Several putative mechanisms of NK cell suppression have been defined in these last years; conversely, the cross talk b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 164 publications
0
62
0
1
Order By: Relevance
“…NK cells are innate immune-effector cells involved in tumor surveillance (10,53,54); however, the functionality of NK cells is altered in patients with cancer (8,10,54), showing reduced degranulation capability and cytotoxicity. Despite their low numbers in TUMs, the presence of CRC infiltrating NK cells can influence patient outcome (14,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are innate immune-effector cells involved in tumor surveillance (10,53,54); however, the functionality of NK cells is altered in patients with cancer (8,10,54), showing reduced degranulation capability and cytotoxicity. Despite their low numbers in TUMs, the presence of CRC infiltrating NK cells can influence patient outcome (14,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 antagonist AMG487 can inhibit metastases in OS murine models, and targeting CXCR3 inhibits metastasis without adversely affecting the host's antitumoral response in breast cancer . However, high natural killer cell infiltration in solid tumors has been reported to be a good prognostic factor, and the recruitment of CXCR3‐positive natural killer cells to the tumor site promotes survival in mouse models of lymphoma and melanoma . Therefore, further studies need to be conducted to better understand the therapeutic effect of targeting CXCR3 in OS.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, high natural killer cell infiltration in solid tumors has been reported to be a good prognostic factor, and the recruitment of CXCR3-positive natural killer cells to the tumor site promotes survival in mouse models of lymphoma and melanoma. 31,32 Therefore, further studies need to be conducted to better understand the therapeutic effect of targeting CXCR3 in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Many solid tumors are encapsulated by a dense layer of the ECM that makes it particularly difficult for immune cells to infiltrate. Several studies have shown that NK and other immune cells tend to accumulate in the stroma of the invasive margin rather than invade the tumor core itself (1,2), ultimately limiting effective antitumor immunity (3).…”
Section: Introductionmentioning
confidence: 99%